Carbon-coated copper catalyst as well as preparation method and application thereof

By using β-cyclodextrin in the hydrogen production reaction of ethanol aqueous phase reforming, the problems of insufficient catalyst activity and poor stability are solved, and efficient hydrogen selectivity and hydrogen production rate are achieved.

CN119633820AActive Publication Date: 2025-03-18GUANGDONG UNIV OF TECH +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411454996.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-18
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

In the hydrogen production reaction of ethanol aqueous phase reforming, the hydrogen selectivity of the existing copper-based catalyst is not high and has poor stability, and the copper active site dispersion is insufficient, resulting in insufficient catalyst activity.

Method used

By using β cyclodextrin as a carbon source, the ratio of β cyclodextrin to copper salt is controlled, and a carbon-coated copper catalyst is prepared under hydrothermal conditions to ensure that the catalyst has stability under reaction conditions and improve the hydrogen production rate and selectivity.

Benefits of technology

The high dispersion and high loading of the catalyst are achieved, the activity and selectivity of the catalyst are improved, the hydrogen production rate and hydrogen selectivity are enhanced, and the long-term stability of the catalyst is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633820A_ABST
    Figure CN119633820A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-coated copper catalyst as well as a preparation method and application thereof, and relates to the technical field of catalysts. According to the technical scheme, beta cyclodextrin is used as a carbon source, so that active component copper-containing particles are uniformly distributed on a carbon coating layer; wherein a carbon coating layer derived after cyclodextrin pyrolysis can effectively inhibit migration and agglomeration of copper active sites, so that the catalyst has relatively high selectivity and relatively good reaction activity, and the catalytic performance of the catalyst is promoted to be improved; the carbon-coated copper catalyst is suitable for catalyzing an ethanol water phase reforming hydrogen production reaction, the hydrogen production rate reaches 35.6 [mu] mol H2 / gcat / s, the hydrogen selectivity is higher than 99.9%, and long-time continuous and stable operation of ethanol water phase reforming hydrogen production can be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and more specifically, to a copper-based catalyst and a preparation method and application thereof. Background Art

[0002] As a clean and efficient form of energy, hydrogen energy has great development potential. The development of hydrogen energy will help promote the transformation and upgrading of the energy structure, reduce dependence on fossil fuels, and improve the flexibility and safety of the energy system. As an emerging method of hydrogen production, ethanol aqueous phase reforming hydrogen production (alkali-free hydrogen production) has the advantages of cheap and easy-to-obtain raw materials, relatively mild reaction conditions, low carbon and environmental protection. Therefore, the development of catalysts for ethanol aqueous phase reforming hydrogen production is of great significance. At present, the catalysts used for low-temperature methanol aqueous phase reforming hydrogen production are mainly precious metal catalysts such as Pt, Pd, Ru, and Rh, which are expensive and not conducive to large-scale industrial production. Copper-based catalysts are inexpensive and have good selectivity and catalytic activity. They have good application prospects in ethanol aqueous phase reforming hydrogen production and are expected to become a substitute for precious metal catalysts. However, in the ethanol / water system, the dispersibility of copper active sites still needs to be improved, and the selectivity for side reaction products carbon monoxide and methane is still high.

[0003] The prior art discloses a preparation method and application of a carbon-coated copper catalyst, wherein the catalyst uses carbon-containing organic matter and an inorganic copper salt solution as main raw materials to prepare a carbon-coated nano copper-based catalyst, which is applied to the ethanol aqueous phase reforming hydrogen production reaction and can effectively improve the selectivity of hydrogen and its reaction rate. However, due to the limitations of the catalyst preparation method, the copper active sites are prone to agglomeration and migration during the drying process, which ultimately leads to uneven distribution on the carrier, thereby causing insufficient catalyst activity. Summary of the invention

[0004] In order to overcome the problems of low hydrogen selectivity and poor stability in the existing ethanol aqueous phase reforming hydrogen production reaction process, the present invention provides a method for preparing a carbon-coated catalyst, by using β-cyclodextrin as a carbon source and controlling the ratio of β-cyclodextrin to copper salt, while ensuring that the carbon-coated copper catalyst has stability under hydrothermal conditions and can effectively improve the hydrogen production rate and selectivity, the speed at which the catalyst reaches its peak hydrogen production performance is accelerated, and its catalytic efficiency is further optimized.

[0005] Another object of the present invention is to provide a carbon-coated copper catalyst obtained by the above preparation method.

[0006] Another object of the present invention is to provide an application of the above-mentioned carbon-coated copper catalyst in hydrogen production by aqueous phase reforming of ethanol.

[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0008] To this end, the first technical solution provided by the present invention is as follows:

[0009] A carbon-coated copper catalyst, comprising copper-containing nanoparticles and a carbon layer coating the copper-containing nanoparticles;

[0010] Calculated based on 100% of the total mass of the carbon-coated copper catalyst, the carbon layer accounts for 23.96-25.47% of the total mass of the catalyst, and the remainder is copper-containing nanoparticles.

[0011] Furthermore, in the above-mentioned carbon-coated copper catalyst, the copper-containing nanoparticles are copper nanoparticles, cuprous oxide nanoparticles or any mixture thereof.

[0012] Furthermore, in the above-mentioned carbon-coated copper catalyst, the total mass of oxygen elements in the cuprous oxide is 18.08% to 21.31% of the total mass of the carbon-coated copper catalyst.

[0013] Furthermore, in the above-mentioned carbon-coated copper catalyst, the median particle size of the copper-containing nanoparticles is 4 to 15 nm.

[0014] The carbon-coated copper catalyst of the present invention uses the organic carbon layer provided by β-cyclodextrin as a carrier to provide attachment sites for the active component copper ions, so that the active sites of copper can be evenly dispersed in the organic carbon layer, which can effectively solve the problem of active component agglomeration, thereby increasing its reaction rate.

[0015] The contents of the organic carbon carrier and the active components monovalent copper and zero-valent copper in the carbon-coated copper-based catalyst are relative. When the carbon content is too high, the content of copper nanoparticles in the catalyst will be reduced, inhibiting its reaction rate and selectivity for hydrogen; when the carbon content is too low, the loading amount of the copper active component will be too high, resulting in agglomeration of active metallic copper, and the copper active sites cannot fully contact with the reactants, thereby reducing the reaction rate.

[0016] In addition, copper nanoparticles are represented by the particle size of the active component, and the particle size of the active component is regulated by the organic carbon content and the interaction force between the active components. The size of the active copper nanoparticles, the organic carbon content and their dispersion state jointly affect the catalytic effect of the carbon-coated copper catalyst in ethanol liquid phase hydrogen production. When the number of copper active sites and the organic carbon content reach a relatively stable equilibrium state, the appropriate active component particle size can be obtained, the dispersion of the active component can be improved, and the catalyst activity can be improved.

[0017] When the particle size of the active component copper nanoparticles is in the range of 4 to 15 nm, the agglomeration of the active component can be effectively suppressed due to the small crystal particle size, and the active component copper nanoparticles can be evenly distributed on the carbon coating layer to achieve high dispersion of copper active sites, thereby improving the activity and selectivity of the carbon-coated copper catalyst.

[0018] The second technical solution provided by the present invention is a method for preparing the above-mentioned nitrogen-doped carbon-coated copper catalyst, comprising the following steps:

[0019] S1. The copper nitrate solution and β-cyclodextrin are mixed and fully complexed, and then dried to obtain a Cu-βCD complex;

[0020] Wherein, the molar ratio of copper nitrate to beta-cyclodextrin is (1.4-6.1):1;

[0021] S2. calcining the Cu-βCD complex prepared in S1 at 200-600° C. for 1-4 h under an inert gas atmosphere to obtain a carbon-coated copper catalyst precursor;

[0022] S3. Reduce the carbon-coated copper-based catalyst precursor in a hydrogen atmosphere to make the copper active sites evenly distributed on the carbon coating layer to obtain a carbon-coated copper catalyst.

[0023] Furthermore, in the above-mentioned method for preparing the nitrogen-doped carbon-coated copper catalyst, the molar ratio of the copper salt to β-cyclodextrin in step S1 is (1.9-5.4):1.

[0024] Furthermore, in the preparation method of the nitrogen-doped carbon-coated copper catalyst, the complexing in step S1 is carried out by stirring at 80° C. for 12 h; and drying is carried out at 80° C. for 24 h.

[0025] Furthermore, in the above-mentioned method for preparing the nitrogen-doped carbon-coated copper catalyst, the calcination temperature in step S2 is 300-400° C., and the calcination time is 2-3 hours.

[0026] Furthermore, in the above-mentioned method for preparing the nitrogen-doped carbon-coated copper catalyst, the reduction temperature in step S3 is 250-550°C.

[0027] The last technical solution provided by the present invention is that the carbon-coated copper catalyst is used to catalyze the reaction of ethanol aqueous phase reforming to produce hydrogen.

[0028] The present invention uses β-cyclodextrin as a carbon source (β-CD). β-cyclodextrin is a cyclic oligosaccharide formed by 7 glucose units bonded by α-1,4-glycosidic bonds. Its molecular shape is slightly conical ring, with a hydrophilic outer surface and a relatively hydrophobic inner cavity. There are hydroxyl groups on the C-2 and C-3 positions of β-cyclodextrin. This hydroxyl group can be used as a ligand to form a coordination bond with copper ions, which is easy to form a complex and has a good dispersion effect on copper active sites. In addition, β-cyclodextrin calcined in an inert atmosphere will form a carbon layer, which can effectively coat copper nanoparticles, provide attachment sites for copper active components, and form a high-load and high-dispersion structure, so that the catalyst has better catalytic performance.

[0029] The particle size, active component loading and carbon content of the copper nanoparticles in the present invention are all affected by the ratio of copper to β-cyclodextrin. Therefore, in order to obtain the carbon-coated copper catalyst described in the present invention, it is necessary to reasonably control the ratio of copper nitrate and β-cyclodextrin so that the active components can be well dispersed under high loading conditions, stabilize the particle size at a small particle size, and further prevent the migration of active components during the reduction of S2 from causing agglomeration when containing high-density active components.

[0030] The purpose of regulating the calcination conditions in the present invention is to ensure the loading amount of carbon and copper nanoparticles and to prevent the agglomeration of active components due to excessively high temperature or the insufficient carbon content due to excessively low temperature.

[0031] The preparation method of the catalyst of the present invention is simple. Beta-cyclodextrin is used as a carbon source and does not need to be carbonized before being stirred and mixed with a metal compound. By controlling the reaction conditions, the prepared carbon-coated copper catalyst has the characteristics of small particle size, high load and high dispersion, and can achieve the effects of high hydrogen production rate, strong hydrogen selectivity and high catalytic activity. It can be used for rapid production of high-purity hydrogen, and is particularly suitable for the field of hydrogen production by aqueous phase reforming of ethanol.

[0032] The invention also protects the use of a carbon-coated copper catalyst in the production of hydrogen by aqueous phase reforming of ethanol.

[0033] The specific application methods are as follows:

[0034] The prepared catalyst is added into a reaction solution of water and ethanol, and argon is used as a protective gas to carry out a hydrogen production reaction in a batch reactor.

[0035] Compared with the prior art, the present invention has at least the following beneficial effects:

[0036] The present invention provides a carbon-coated copper catalyst, which constrains the migration and agglomeration of copper nanoparticles of an active component through a carbon layer and provides attachment sites for the active component, thereby obtaining a high-loaded and highly dispersed nitrogen-doped carbon-coated copper catalyst. The catalytic performance of the catalyst is improved by controlling the active component loading amount, carbon content and particle size of the active component of the carbon-coated copper catalyst, and the catalyst has high catalytic activity and good hydrothermal stability.

[0037] The carbon-coated copper catalyst of the present invention is particularly suitable for catalyzing hydrogen production from liquid-phase reforming of methanol, has a high hydrogen production rate and high hydrogen selectivity, the selectivity of hydrogen in the produced gas is higher than 99.9%, the hydrogen production rate can reach 35 μmol H2 / gcat / s, and can operate continuously and stably for 400 hours on a fixed bed reactor. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the infrared spectrum of the carbon-coated copper catalyst.

[0039] Figure 2 Scanning electron microscopy (SEM) image of carbon-coated copper catalyst (left) and the corresponding HRTEM image of carbon-coated copper catalyst (right).

[0040] Figure 3 High-angle annular dark field transmission electron microscopy (HAADF-STEM) image of the carbon-coated copper catalyst and an enlarged HRTEM image of the Cu nanoparticle structure coated with the carbon layer.

[0041] Figure 4 It is a comparison chart of the performance of the carbon-coated copper catalyst, CuZnAl commercial catalyst, and Raney Cu commercial catalyst for ethanol aqueous phase reforming to produce hydrogen.

[0042] Figure 5 XRD spectra of carbon-coated copper catalysts with different molar ratios of copper nitrate and β-cyclodextrin.

[0043] Figure 6 XRD spectra of carbon-coated copper catalyst before and after the reaction. DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0045] Example 1

[0046] This embodiment provides a carbon-coated copper catalyst for ethanol aqueous phase reforming to produce hydrogen, which is prepared by the following steps:

[0047] S1. Mix copper nitrate and β-cyclodextrin, stir at 80° C. for 12 h to fully complex, and then fully dry at 80° C. to obtain a Cu-CD complex; wherein the molar ratio of copper nitrate to β-cyclodextrin is 4:1;

[0048] S2. The Cu-CD composite in S1 was calcined at 400 °C for 2 h under a nitrogen atmosphere to obtain a carbon-coated copper precursor;

[0049] S3. 50 mg of carbon-coated copper catalyst precursor was reduced at 350° C. for 2 h at a hydrogen flow rate of 50 ml / min to obtain a carbon-coated copper catalyst. The components and their contents in the catalyst are shown in Table 1.

[0050] Example 2

[0051] This embodiment provides another carbon-coated copper catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination temperature used in S2 is 300°C. Please refer to Table 1 for the components and contents of the catalyst.

[0052] Example 3

[0053] This embodiment provides another carbon-coated copper catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination temperature used in S2 is 450°C. Please refer to Table 1 for the components and contents of the catalyst.

[0054] Example 4

[0055] This embodiment provides another carbon-coated copper catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination time in S2 is 1 h. Please refer to Table 1 for the components and contents of the catalyst.

[0056] Example 5

[0057] This embodiment provides another carbon-coated copper catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination time in S2 is 3 hours. Please refer to Table 1 for the components and contents of the catalyst.

[0058] Example 6

[0059] This embodiment provides another carbon-coated copper catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination time in S2 is 1 h and the calcination temperature is 300°C. Please refer to Table 1 for the components and contents of the catalyst.

[0060] Example 7

[0061] This embodiment provides another carbon-coated copper catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination time in S2 is 3 hours and the calcination temperature is 300°C. Please refer to Table 1 for the components and their contents in the catalyst.

[0062] Example 8

[0063] This embodiment provides another carbon-coated copper catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the calcination time in S2 is 1 h and the calcination temperature is 300°C. Please refer to Table 1 for the components and contents of the catalyst.

[0064] Table 1

[0065]

[0066]

[0067] By infrared spectroscopy analysis of raw material βCD and Cu-βCD complex, refer to Figure 1 It is judged that the copper ions provided by copper nitrate and β-cyclodextrin form a complex through coordination. Through infrared spectrum observation, βCD has a wavelength of 3200-3600cm -1 The signal at 3200-3600 cm-1 is the vibration of OH, while the signal at 3200-3600 cm-1 on the Cu-βCD complex is the vibration of OH. -1 The OH vibration signal is significantly weakened. This proves that the copper ions provided by copper nitrate and β-cyclodextrin may form a complex by coordinating with the oxygen-containing functional group OH, so that the copper nanoparticles can be evenly distributed on the organic carbon layer after calcination, and the particle size is small and has high dispersibility.

[0068] For the SEM images of the carbon-coated copper catalyst and the corresponding HRTEM images of the carbon-coated copper catalyst, please refer to Figure 2 ; Through SEM observation, the carbon-coated copper catalyst has a thin block structure, indicating that there is a large contact area between the catalyst and the reactants and the reaction rate is high. From the HRTEM image of the carbon-coated copper catalyst, it can be seen that the copper nanoparticles in the carbon-coated copper catalyst are small in size and evenly distributed, indicating that the carbon-coated copper catalyst has achieved a highly dispersed loading of active metal copper on the carrier, which shows that the catalyst is a catalyst with high dispersion and can effectively catalyze the hydrogen production reaction of ethanol aqueous phase reforming.

[0069] High-angle annular dark field transmission electron microscopy (HAADF-STEM) image of a carbon-coated copper catalyst and a magnified HRTEM image of the carbon-coated Cu nanoparticle structure, see Figure 3It can be seen that the copper nanoparticles in the carbon-coated copper catalyst have a particle size of about 10 nm and are evenly distributed on the carbon coating layer without accumulation, effectively maintaining a high number of active sites and the long-term stability of the catalyst.

[0070] Comparative Example 1

[0071] This comparative example provides a carbon-coated copper catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the molar ratio of copper nitrate to β-cyclodextrin is 2.6:1. Please refer to Table 2 for the components and contents of the catalyst.

[0072] Comparative Example 2

[0073] This comparative example provides a carbon-coated copper catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the molar ratio of copper nitrate to β-cyclodextrin is 3.3:1. Please refer to Table 2 for the components and contents of the catalyst.

[0074] Comparative Example 3

[0075] This comparative example provides a carbon-coated copper catalyst for ethanol aqueous phase reforming to produce hydrogen. Its preparation method is basically the same as that of Example 1, except that the molar ratio of copper nitrate to β-cyclodextrin is 4.7:1. Please refer to Table 2 for the components and contents of the catalyst.

[0076] Table 2

[0077]

[0078]

[0079] Note: The copper nanoparticle loading described in this application refers to metallic copper, and the total mass of copper in cuprous oxide accounts for the total mass percentage of the catalyst.

[0080] Comparative Examples 4 to 8

[0081] Comparative Examples 4 to 8 provide a carbon-coated copper catalyst for producing hydrogen by aqueous phase reforming of ethanol, the preparation method of which is basically the same as that of Example 1, except that the carbon source is different, see Table 3 for details.

[0082] Table 3

[0083] Comparative Example Organic carbon source Comparative Example 4 glucose Comparative Example 5 Sorbitol Comparative Example 6 Agar Comparative Example 7 Konjac Gum Comparative Example 8 Agarose

[0084] Comparative Example 9

[0085] The purchased CuZnAl commercial catalyst was ground and crushed, and 50 mg of the catalyst was weighed and reduced at 350° C. for 2 h at a hydrogen flow rate of 50 ml / min.

[0086] Comparative Example 10

[0087] The purchased Raney Cu commercial catalyst was ground and crushed, and 50 mg of the catalyst was weighed and reduced at 350° C. for 2 h at a hydrogen flow rate of 50 ml / min.

[0088] Results

[0089] The catalytic reaction conditions of the carbon-coated copper catalyst in ethanol aqueous phase reforming to produce hydrogen are as follows:

[0090] 50 mg of any one of the catalysts described in Examples 1-8 and Comparative Examples 1-10 was added to 20 ml of ethanol aqueous solution in a batch reactor, and 2 MPa argon was used as a protective gas. After reacting at 210° C. for 2 h, the gas phase product was quantitatively analyzed by gas chromatography after cooling to room temperature. The results are shown in Table 4.

[0091] The ethanol aqueous solution is composed of ethanol and water in a molar ratio of 1:1.

[0092] The hydrogen production rate of the carbon-coated copper catalyst is calculated by the water displacement method based on the gas production volume, and the hydrogen production rate is the μmol hydrogen content produced per gram of catalyst per second; the selectivity is calculated by the amount of H2, CO, and CH4 in the product, for example, hydrogen selectivity H2 (%) = nH2*100% / (nH2+nCO+nCH4).

[0093] Table 4 Comparison of catalytic effects of various embodiments and comparative examples

[0094]

[0095] It can be seen from Examples 1 to 3 that when the calcination temperature varies in the range of 300°C to 450°C, the catalyst obtained by calcining at 400°C has the best performance. The calcination temperature of 400°C can promote the formation of sufficient pores inside the carbon-coated copper catalyst, increase the specific surface area and active sites, and thus make the catalyst have higher activity. However, the copper nanoparticles in the carbon-coated copper catalyst obtained by calcining at 300°C are difficult to disperse and the catalytic rate is low; the copper nanoparticles in the carbon-coated copper catalyst obtained by calcining at 450°C agglomerate, the reaction area with ethanol water becomes smaller, and the reaction rate decreases; it can be seen from Examples 4 to 8 that the longer the calcination time, the better the performance of the catalyst. When the calcination time is too short, although the particles are dispersed more evenly, the active components in the catalyst have not completely formed an ideal crystal structure, resulting in an imperfect structure and distribution of the active sites, and the target product cannot be effectively selected in the ethanol aqueous phase reforming hydrogen production reaction, thereby reducing the selectivity. When the calcination time is too long, the catalyst pore structure will collapse, resulting in the diffusion of active sites being blocked, resulting in a decrease in the activity of the catalyst and a decrease in the hydrogen production rate. It can be seen from Example 1 and Comparative Examples 1 to 3 that the performance of the catalyst is different when the proportion of β-cyclodextrin providing the carbon source is changed. When the proportion of β-cyclodextrin increases or decreases, the hydrogen production rate will decrease, and the selectivity of hydrogen will also decrease. It can be seen from Example 1 and Comparative Examples 4 to 8 that the hydrogen production performance of the catalyst prepared by using β-cyclodextrin as an organic carbon source is better than that of other catalysts such as sorbitol or glutamic acid that use it as an organic carbon source. This is because β-cyclodextrin has a special ring structure and can form inclusion compounds. This structural characteristic enables it to better combine with copper elements when preparing copper-based catalysts to form stable and efficient catalytic active centers; in addition, different organic carbon sources have different abilities to promote the dispersion of active metal copper during coupling, which ultimately leads to different hydrogen production rates.

[0096] from Figure 4 As can be seen from Table 4, the selectivity of hydrogen in the gas produced by the carbon-coated copper in Example 1 at 210°C is 99.79%, and the selectivity of carbon monoxide is less than 0.1%, which is better than the CuZnAl commercial catalyst and the Raney Cu commercial catalyst, achieving effective separation of the reaction products and greatly reducing the purification cost. The hydrogen production rate of the carbon-coated copper catalyst is as high as 35.6μmol·gcat-1·s-1, which is 1.52 times the hydrogen production rate of the CuZnAl commercial catalyst under the same conditions and 1.38 times that of the Raney Cu commercial catalyst, achieving a huge breakthrough in the application of non-precious metal catalysts in the production of hydrogen by aqueous phase reforming of ethanol.

[0097] Figure 5The XRD spectrum of the carbon-coated copper catalyst prepared by changing the ratio of copper nitrate to β-cyclodextrin shows that as the molar ratio of Cu to β-cyclodextrin decreases from 4.01 to 2.6, or increases from 4.0 to 4.7, the characteristic peak of copper presented in the XRD spectrum gradually becomes sharper, and the particle size of the copper nanoparticles increases. When the particle size of the copper nanoparticles increases, the organic carbon cannot effectively coat the active components of copper. This leads to the aggregation of copper active sites during the sintering process, and the contact area with ethanol water is also reduced. Ultimately, this will lead to a decrease in hydrogen production rate and selectivity.

[0098] Figure 6 The XRD spectra of the carbon-coated copper catalyst before and after the reaction are shown in Figure 2. By comparing the XRD spectra of the carbon-coated copper catalyst before and after the reaction, it can be found that the peak sharpness and shape of the XRD spectra do not change much, and the size of the active metal copper nanoparticles does not increase significantly, which shows that the carbon-coated copper catalyst has good stability and its structure remains basically consistent during the reaction.

[0099] It should be noted that although the remaining embodiments provide relevant descriptions of their corresponding XRD spectra, transmission electron microscope images, and elemental analysis images, their relevant performances are equivalent.

[0100] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention shall be included in the protection scope of the claims of the present invention.

Claims

1. A carbon-coated copper catalyst, characterized in that The carbon-coated copper catalyst comprises copper-containing nanoparticles and a carbon layer coating the copper-containing nanoparticles; Calculated based on 100% of the total mass of the carbon-coated copper catalyst, the carbon layer accounts for 23.96-25.47% of the total mass of the catalyst, and the remainder is copper-containing nanoparticles.

2. The carbon-coated copper catalyst according to claim 1, characterized in that The copper-containing nanoparticles are copper nanoparticles, cuprous oxide nanoparticles or any mixture thereof.

3. The carbon-coated copper catalyst according to claim 2, characterized in that The total mass of oxygen elements in the cuprous oxide is 18.08% to 21.31% of the total mass of the carbon-coated copper catalyst.

4. The carbon-coated copper catalyst according to claim 1, characterized in that The median particle size of the copper-containing nanoparticles is 4 to 15 nm.

5. A method for preparing the nitrogen-doped carbon-coated copper catalyst according to any one of claims 1 to 4, characterized in that: The steps include: S1. The copper nitrate solution and β-cyclodextrin are mixed and fully complexed, and then dried to obtain a Cu-βCD complex; Wherein, the molar ratio of copper nitrate to beta-cyclodextrin is (1.4-6.1):1; S2. calcining the Cu-βCD complex prepared in S1 at 200-600° C. for 1-4 h under an inert gas atmosphere to obtain a carbon-coated copper catalyst precursor; S3. Reduce the carbon-coated copper-based catalyst precursor in a hydrogen atmosphere to make the copper active sites evenly distributed on the carbon coating layer to obtain a carbon-coated copper catalyst.

6. The method for preparing the nitrogen-doped carbon-coated copper catalyst according to claim 5, characterized in that: The molar ratio of the copper salt to β-cyclodextrin in step S1 is (1.9-5.4):

1.

7. The method for preparing the nitrogen-doped carbon-coated copper catalyst according to claim 5, characterized in that: The complexation in step S1 is carried out by stirring at 80° C. for 12 h; and drying is carried out at 80° C. for 24 h.

8. The method for preparing the nitrogen-doped carbon-coated copper catalyst according to claim 5, characterized in that: The calcination temperature in step S2 is 300-400° C., and the calcination time is 2-3 hours.

9. The method for preparing the nitrogen-doped carbon-coated copper catalyst according to claim 5, characterized in that: The reduction temperature in step S3 is 250-550°C.

10. The carbon-coated copper catalyst according to any one of claims 1 to 4 is used to catalyze the reaction of ethanol aqueous phase reforming to produce hydrogen.

Citation Information

Patent Citations

  • Preparation method and application of carbon-coated nano copper-zinc-aluminum catalyst

    CN109046362A

  • Nitrogen-doped carbon-coated copper catalyst as well as preparation method and application thereof

    CN115770603A

  • Copper-based catalyst as well as preparation method and application thereof

    CN116889869A

  • Cu (at) pCN catalyst as well as preparation method and application thereof

    CN117861709A

  • Catalyst, electrode catalyst, and manufacturing method of electrode catalyst

    JP2018024895A